AN EVALUATION OF READING MATERIALS IN “ENGLISH IN FOCUS” TEXTBOOK FOR SEVENTH GRADE STUDENTS IN ONE OF JUNIOR HIGH SCHOOLS IN BANDUNG - Inge Rakhma Kanina (Journal of English and Education, 2016)
This study was intended to evaluate the reading materials on “English in Focus” textbook for seventh grade students published by the National Department of Education in Indonesia in 2008 based on good reading materials and to investigate the teachers’ perception about the textbook. The evaluation criteria is based on the good reading materials criteria by Patel and Jain (2008). The study was employed descriptive- qualitative method with checklist and interview as its instrument to collect and identify the data. The results show that the reading materials in the textbook fulfill the criteria of good reading materials. Furthermore, the results from the interview show that the teachers’ perception about the book is sufficiently good.